Single-cell omics reveals arg-1 as a key regulator of age-dependent macrophage-mediated cartilage repair - JianJun Chu; Zhengfa Wen; Wenying Wu; Shoukun Wu (PLoS ONE, 2026)
Aging impairs cartilage repair, with young animals exhibiting superior regenerative capacity due to enhanced tissue repairing and reduced inflammation compared to aged counterparts. This study employed single-cell omics to dissect age-dependent immune cell heterogeneity in cartilage injury, revealing a critical deficiency in anti-inflammation macrophage subsets in aged animals. We identified Arg-1 as a central regulator of macrophage polarization, demonstrating that its overexpression rescues impaired repair in aged animals. These findings establish Arg-1 as a novel therapeutic target to counteract age-related declines in cartilage regeneration, offering new insights into macrophage-driven tissue repair mechanisms. The integration of single-cell analysis with functional validation provides a framework for developing precision interventions for age-impaired tissue regeneration.